A Babel suspeita de Nelson de Oliveira - José Leonardo Tonus (Universidade de Brasília, 2011)
The photomontages made by artist Teresa Yamashita included in the anthology Babel Babilônia from brazilian writer Nelson de Oliveira published in 2007, sug- gests the presence of a pictorial story concomitantly that, with also the paratex- tuals devices and all narratives, requires for a reflection on the crisis values that runs through our society. They create an effect of redundancy that, in addiction to ensuring the readability speech, pointed of an authorial voice that committed us to ask ourselves about the functions and limits of semantic-pragmatic relations between text, image, intertext and architext.